2013
DOI: 10.3329/jsr.v5i3.14055
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Ganoderma lucidum on Paracetamol-induced Acute Hepatotoxicity in Rats

Abstract: The preventive effect of Ganoderma lucidum on paracetamol-induced acute hepatotoxicity was investigated in Wistar rats in the present study. Hepatotoxicity was induced by oral administration of paracetamol (500 mg/kg of body weight) for the last 7 consecutive days of the dietary of regimen G. lucidum. The extent of liver damage was determined by assessing the plasma levels of alanine aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), total bilirubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The disruption of hepatocyte membrane permeability by APAP intoxication allows these enzymes to leak out from the liver cytosol into the blood circulation, thus inducing necrosis and inflammatory responses [ 25 , 29 ]. Our findings are consistent with those of some previous studies [ 25 , 26 ]. Pretreatment with EECM tended to alleviate the activities of the serum transaminases, ALP and LDH, thereby demonstrating that EECM maintained membrane integrity and restricted the leakage of hepatic enzymes via a mechanism that is not yet completely understood.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The disruption of hepatocyte membrane permeability by APAP intoxication allows these enzymes to leak out from the liver cytosol into the blood circulation, thus inducing necrosis and inflammatory responses [ 25 , 29 ]. Our findings are consistent with those of some previous studies [ 25 , 26 ]. Pretreatment with EECM tended to alleviate the activities of the serum transaminases, ALP and LDH, thereby demonstrating that EECM maintained membrane integrity and restricted the leakage of hepatic enzymes via a mechanism that is not yet completely understood.…”
Section: Discussionsupporting
confidence: 94%
“…The animal experiments were designed based on the findings of the effective dose of acetaminophen as an agent for liver damage at subacute exposure while the outcomes of the study are the effects of C. macroptera investigated at multiple doses with some modifications ( Figure 1 ) [ 13 , 26 ]. Briefly, the animals were randomly divided into seven groups with six rats in each group.…”
Section: Methodsmentioning
confidence: 99%
“…125 mcg G. lucidum extract is the dose-dependent manner which significantly reduced serum LDH levels compared with that of positive control group. These results are in agreement with Rahman and Hossain, (2013) 31 who has studied the protective effect of G. lucidum on acute hepatotoxicity using paracetamol for the induction of liver damage and demonstrate that the G. lucidum has significant hepatoprotective activity against paracetamol -induced acute hepatotoxicity and reported that G. lucidum significantly decreased the plasma levels of LDH in rats nearly to those of the normal control. This coincides also with Xu et al, (2017) 32 who has studied cardioprotective effects of G. lucidum polysaccharides (GLPS) on DOXinduced cardiotoxicity and associated serum LDH release which is also an indicator of cell injury and found that DOX injection significantly elevated serum levels of LDH ; however GLPS pre-treatment significantly reversed the levels of these cardiac enzymes and obviously prevented LDH leakage as well as significantly decreased the serum levels of LDH.…”
Section: Biochemical Parameters Lactate Dehydrogenase (Ldh) Levelsupporting
confidence: 91%
“…Therefore searching for agents capable of reducing the levels of Pb from the body could be considered as one of the important preventive measures. Very recently, we have reported that the oral administration of G. lucidum extract prevents paracetamol-induced hepatotoxicity in rats [ 19 ] and erythrocyte hemolysis in rats [ 20 ], suggesting oral administration of this medicinal mushroom extract can play, at least partially, role in the reduction of Pb-induced hemolysis and related anemia. In this study, we thus investigated whether the chronic administration of Pb results in an increased sensitivity of erythrocyte to hemolysis and, if so, then whether the oral administration of the extract of G. lucidum decreases it.…”
Section: Introductionmentioning
confidence: 99%